Molecular bases of muscular definition: the role of myostatin and proteinkinase β in progression of protein-energy waste in patients on hemodialysis - A. S. Kuzyarova; M. Z. Gasanov; M. M. Batyushin; O. V. Golubeva (Архивъ внутренней медицины)
Improving the nephrology service and increasing the availability of hemodialysis create the prerequisites for a deeper analysis of the associated complications and associated diseases. One of the main clinical conditions that worsen the patient’s prognosis is protein-energy deficiency (BPH), which is manifested by loss of muscle mass, strength and performance of skeletal muscles, which also leads to a decrease in quality of life, and often to disability and death.The aim: assess of the relationship between myostatin and protein kinase β, as markers of the catabolic cascade, with the manifestations of PEW in hemodialysis patients.Materials and methods: 80 people took part in the study (47 men and 33 women), the median age was 51.7 ± 11.6 years. All patients had CKD 5D stages with chronic hemodialysis treatment for an average duration of 33.5 (0.5; 236) months. All patients were carried out a detailed clinical and anamnestic examination, we estimated the anthropometric measurement, muscular strength were using the hand dynamometry method. The levels of MSTN and AKT were determined in serum by enzyme immunoassay (ELISA Kit, USA). Statistical analysis was carried out using STATISTICA 10.0 (StatSoft Inc., USA) and Microsoft Office Excel 2010 (Microsoft Corp., USA).Results: A dependence of the local increase in skin folds with an increase in the MSTN level, as well as a decrease in the thickness of the subcutaneous fatty tissue with a decrease in AKT (p = 0.03) was detected. We proposed a muscle catabolism index for assessing the degree of muscle degradation. IT had a statistically proven association with degree PEW and clinical manifestations of it. Analysis of the effects of markers of systemic inflammation with MSTN did not give statistically significant results. However, in the subgroup with elevated AKT with the activation of anabolic processes, we observed a decrease in β2-microglobulin and an increase in serum iron (p = 0.04). In the subgroup with a high level of MSTN, higher concentrations of parathyroid hormone (PTH) were determined. We found a direct correlation between the increase in protein kinase β and the annual PTH fluctuation (r = 0.83, p = 0.01).Conclusion. In our study, we were found that in patients with CKD5D receiving therapy with chronic hemodialysis, the activity of myostatin and protein kinase β varies. This leads to an increase in protein degradation over the processes of synthesis, which creates prerequisites for the development of sarcopenia. Taking into account the data obtained, further study of the intermolecular interactions of these markers in the catabolic cascade of muscle proteins is of research interest.